Teaching High School Students and College Freshmen Product Development by Deterministic Design With PREP (2007)
ABSTRACT: This paper describes an effective method for teaching design in a deterministic manner that is especially effective for under-represented students (e.g., culture, race, gender, physical disability, personality, etc.). Ten years ago we postulated that students can learn a deterministic design process not only to learn about design, but to better study math and science with peers through the use of an ordered peer-review process. The foundation of Deterministic Design is that everything happens for a reason (science, e.g., physics) and a systematic approach should be used first by individuals in a team to ask and answer questions. To ensure participation and to check that items have not been overlooked, work by individuals is followed by a Peer-Review Evaluation Process (PREP) and then the team brainstorms. Deterministic Design has designers describing what is to be done (functional requirements), how it can be done (design parameters), why it will work (analysis), who else has done similar work (references), and what are the risks and possible countermeasures. PREP is especially useful for diverse teams of designers with members from various backgrounds and personalities. It is also especially useful for enabling introverted team members to fully contribute to the development of designs.